Understanding gambling in the United Kingdom: A qualitative study on the experiences of gamblers’ families - Azemi, Ferid; Avdyli, Merita; Bytyqi, Vilard (Frontiers in Psychology, 2023)
This study focuses on understanding the experiences of family members of problem gamblers in the United Kingdom and the gambling consequences in their lives. Family members of problem gamblers, even though they suffer from gambling consequences, the impacts of gambling are under-researched. Qualitative research through in-depth interviews was employed. Thematic analysis was used to gain a deeper insight into gambling. Nine female participants were interviewed based on a semi-structured questionnaire. The results of this study indicated that close family members of problem gamblers had suffered not only financial devastation but also harsh psychological and mental health damages. Furthermore, family members suffer from gamblers' abusive and violent behaviors. Addiction was a key factor of gamblers' habit; fear, anxiety, and depression were some of the health issues derived from gambling. Overall, gambling addiction leads to further addiction, crime, and also severe, family-relation sufferings. The study results suggest that the London Gambling Commission and regulating authority should change gambling policy, reduce gambling points, and limit gambling slot machines in food markets and community areas. More support is needed for family members affected by gamblers’ addictive gambling behaviors.